Detection of volatile organic compound gas using localized surface plasmon resonance of gold nanoparticles - Sri Nengsih,; Akrajas Ali Umar,; Muhamad Mat Salleh,; Muhammad Yahaya, (Universiti Kebangsaan Malaysia, 2011)
This paper reports on the detection of several organic vapors using the unique characteristic of localized surface plasmon resonance (LSPR) gold nanoparticles. Gold nanoparticles on quartz substrate were prepared using seed mediated growth method. In a typical process, gold nanoparticles with average size ca. 36 nm were obtained to densely grown on the substrate. Detection of gas was based on the change in the LSPR of the gold nanoparticles film upon the exposure to the gas sample. It was found that gold nanoparticles were sensitive to the presence of volatile organic compound (VOC) gas from the change in the surface plasmon resonance (SPR) intensity. The mechanism for the detection of VOC’s gas will be discussed